Setup Time Measurement on Flexo 4 Using The Single-Minute Exchange of Dies (SMED) Method in a Multi-Group Cardboard Production Setting - Riyanti, Popy Dian; Amalia, Amalia (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Long and unstandardized setup times are a major source of inefficiency in the cardboard packaging production process, particularly on the Flexo 4 machine, which requires 1.5 to 2 hours for setup. This study aims to reduce setup time by implementing the SMED (Single-Minute Exchange of Dies) method. Three internal activities—ink retrieval, material preparation, and plate preparation—were converted into external activities, reducing setup time by up to 66.67%. Observations were made on three work groups during shift 1, with average setup times ranging from the longest to the shortest: Group C (33.9 minutes), Group A (32.3 minutes), and Group B (30.05 minutes). ANOVA results show no significant differences between the groups. The longest setup time occurred in Group C, with 7,500 pcs and 4 plates, taking 75 minutes. This was due to the Mounting Plate process and limited operator resources.